(untitled) (Global Journal of Human-Social Science, 2020)
The aim of this paper is to demonstrate how to draw out a meaningful formulation of a person s life with the aid of the Art of Meaning semi-structured interview A qualitative research method of a one-on-one interview designed by a philosophical interpretation approach is employed The formulated meaning the outcome of the Art of Meaning interview is analyzed through a basic qualitative interpretation A mutually satisfying formulation is created with the collaboration of the interviewee A Warm Welcome was the outcome of a specific interview which I held with an American philosopher Discussion avers that meaning appears at the overlap of self-identity and worldview It corroborates the postulate that meaningfulness surfaces through strong connections among self others and the world The formulated meaning draws a line connecting fundamental life decisions and values